Measuring the Quality of a Master's Program Course in Public Administration - Horia Mihai RABOCA; Adina SOLOMON (Transylvanian Review of Administrative Sciences, 2010)
Student satisfaction can be measured using the concept of disconfirmation. Disconfirmation is the difference between the expectations concerning a service. Using regression analysis and the concept of disconfirmation, easily interpretable graphical displays can be produced to identify areas that are important to student satisfaction. This article illustrates that there are some components (dimensions) related to courses which have a positive impact on student satisfaction.